Coping With Stress For Mothers Who Have Children With Speech Delay - Ulfa Mahira; Rika Widya; Rahayu Dwi Utami (Yayasan Multidimensi Kreatif, 2025)
Speech delay is a common developmental disorder in preschoolers aged 3 to 5 years, significantly affecting their cognitive, emotional, and social development. This study aims to explore the mechanism of coping stress applied by mothers of children with speech delays. This study uses a qualitative method, in-depth interviews were conducted with three mothers at Panglima Semesta Kindergarten, Medan Tuntungan. The findings showed that the coping mechanism of each mother was different, some used emotion focused coping and some used problem focused coping. Every mother also experiences obstacles such as the absence of support from family and difficult access to services.